Local South African understandings of persistent crying in infants: perceptions of health care workers and traditional healers - Mbongwa, Cynthia Nompumelelo (My University, 2022)
More often than not challenges that are experienced in early infancy may be precursors of the development of mental health problems for both the infant and the mother. One commonly under-researched challenge of parenting is sitting with an inconsolable, excessively crying infant. This research aims to explore the encounters with and reflections of local health care practitioners’ with excessively crying babies in South Africa, and their understandings of this phenomenon. Including participants from both Western-medical and traditional healing orientations, the study explores culturally and contextually situated conceptualisations and understandings of excessively crying infants and highlights convergences and divergences between traditional cultural understandings and Western medical approaches. The study employed a qualitative research approach, and utilised a social constructionist paradigm, allowing for exploration of the understandings related to the management of persistent infant crying within black South African culture. Data collection was in a form of eight semi structured in-depth online interviews with health care practitioners who have experience working with mothers and persistently crying infants. An interpretive thematic analysis was used to analyse the interviews. Key findings that emerged indicated that cultural frameworks ascribe persistent crying in infants to the influence of supernatural powers. However, significant overlaps with Western medical and psychological worldviews were also evident. The main conclusion reached was that mothers often straddle both local, culturally sanctioned care and Western medical approaches in their navigations of health care for their infants and require respectful support from health care professionals.
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Clinical Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2022